Biological Sampling, Fish Nest Monitoring - Sean, Vichet; Ou, Phichong; Freed, Sarah; Sun, Vathanak (2024)
The purpose of this research, monitoring and evaluation is to report on required indicators and evaluate the effectiveness of CFR interventions on 1) Improving fish biodiversity within the CFR, as assessed by Biological monitoring and 2) Improving maintenance of fish biomass and abundance within the CFR during the dry season (Nov-May), as assessed by Biological monitoring Five CFR project sites will be selected as treatment sites and three unmanaged water bodies will be selected as control sites, for a total of eight sites to receive biological sampling. Treatment sites will be selected to represent two or three CFR ‘types’, based on connectivity and size of the water body. Control and treatment sites will be matched or grouped based on the following features: size and depth of water body (including wet season and dry season sizes and depths), distance from river or other large water body, number of inlets connecting the water body to surrounding landscape, and average elevation of the water body.